2022
DOI: 10.3389/fmolb.2021.774215
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylated PCDHGB7 as a Biomarker for Early Detection of Endometrial Cancer in Endometrial Brush Samples and Cervical Scrapings

Abstract: Endometrial cancer (EC) is one of the most common gynecologic cancers in developed countries. Presently, it is imperative to develop a reliable, noninvasive, or minimally invasive detection method for EC. We explored the possibility of using DNA methylation marker from endometrial brush samples (with a “Tao brush”) and cervical scrapes (with a “Pap brush”) for early detection of EC. We analyzed the methylation data of EC and normal endometrial tissues from The Cancer Genome Atlas (TCGA) and Gene Expression Omn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Similarly, previous reports documented 3-gene panel (BHLHE22-CDO1-CELF4/BHLHE22-CDO1-TBX5) or single gene-based (PCDHGB7) DNA methylation for EC detection using cervical scrapings, the ROC for these markers ranged from 0.80 to 0.94, or 0.86, respectively. 11 13 Also, Wang et al 26 reported a relevant study on methylation marker-based EC screening in endometrial cytological samples using Li Brush. Compared with endometrial sampling, cervical Pap brush sampling is a more acceptable screening tool for the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, previous reports documented 3-gene panel (BHLHE22-CDO1-CELF4/BHLHE22-CDO1-TBX5) or single gene-based (PCDHGB7) DNA methylation for EC detection using cervical scrapings, the ROC for these markers ranged from 0.80 to 0.94, or 0.86, respectively. 11 13 Also, Wang et al 26 reported a relevant study on methylation marker-based EC screening in endometrial cytological samples using Li Brush. Compared with endometrial sampling, cervical Pap brush sampling is a more acceptable screening tool for the general population.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Similar studies furthermore demonstrated that cervical scrapings, instead of endometrium and blood, are a good source of DNA for molecular testing, and DNA methylated genes as biomarkers for EC detection from cervical scrapings is feasible and appealing. 11 13 However, relevant research is relatively uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gene methylation, especially in ADCYAP1 and HAND2 , can be identified prior to the diagnosis of EC [ 42 ]. Hypermethylated PCDHGB7 has been identified as a new cancer marker and is applicable in early screening for EC and CC [ 43 ]. Thus, abnormal DNA methylation could serve as a promising indicator for the detection of EC and CC.…”
Section: Targeting Epigenetic Modifiers In Gynecological Cancersmentioning
confidence: 99%
“…Previously, we have proposed the concept of universal cancer–only methylation (UCOM), a collection of cancer-specific epigenetic features shared among most cancer types ( 24 , 25 ). The clinical value of several markers has already been demonstrated in early diagnosis of specific cancer types, including lung cancer, cervical cancer, and endometrial cancer ( 24 , 26 , 27 ). However, the clinical utility of their pan-cancer characteristics remains to be demonstrated in a real-world study with diverse tumor types.…”
Section: Introductionmentioning
confidence: 99%